2017
DOI: 10.1111/ane.12775
|View full text |Cite
|
Sign up to set email alerts
|

Viruses and endogenous retroviruses in multiple sclerosis: From correlation to causation

Abstract: Multiple sclerosis is an immune-mediated disease with an environmental component. According to a long-standing but unproven hypothesis dating to initial descriptions of multiple sclerosis (MS) at the end of the 19th century, viruses are either directly or indirectly implicated in MS pathogenesis. Whether viruses in MS are principally causal or simply contributory remains to be proven, but many viruses or viral elements-predominantly Epstein-Barr virus, human endogenous retroviruses (HERVs) and human herpesviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 148 publications
(148 reference statements)
0
30
0
4
Order By: Relevance
“…However, the clinical relevance-with respect to whether these alterations contribute towards susceptibility for MS or, instead, they exert a relative protective effect-remains controversial both for adult [53,54] and pediatric populations [55,56]. In 2016, two case control studies reported distinct patterns of gut microbiota composition by the use of 16S ribosomal ribonucleic acid rRNA metagenomics analysis [57,58] (for further discussion on the potential of metagenomic techniques as applied to MS, see [59,60]). These studies provided evidence of reduced diversity in the gut microbiome of MS patients compared to controls.…”
Section: Mechanisms Of Immune-modulation By Intestinal Microbiota-climentioning
confidence: 99%
See 1 more Smart Citation
“…However, the clinical relevance-with respect to whether these alterations contribute towards susceptibility for MS or, instead, they exert a relative protective effect-remains controversial both for adult [53,54] and pediatric populations [55,56]. In 2016, two case control studies reported distinct patterns of gut microbiota composition by the use of 16S ribosomal ribonucleic acid rRNA metagenomics analysis [57,58] (for further discussion on the potential of metagenomic techniques as applied to MS, see [59,60]). These studies provided evidence of reduced diversity in the gut microbiome of MS patients compared to controls.…”
Section: Mechanisms Of Immune-modulation By Intestinal Microbiota-climentioning
confidence: 99%
“…MS is a complex autoimmune disease with clinical variability. As such, the establishment of a causative role for intestinal microbiota towards disease pathogenesis requires combined efforts from the field of metagenomics and other "-omics" approaches [59,60,111] with the capacity for high throughput data production and the application of these data in the context of translational medicine.…”
Section: Conclusion: Treat the Microbiome-treat Ms?mentioning
confidence: 99%
“…Over 30 y ago, infection with exogenous human lentiviruses was suspected (8), but differences in the presence of retroviral genome between MS and controls (9) or antibodies (10) to several retroviruses were not confirmed. It appears that, if a human retrovirus is involved, it is more likely to be through activation of retroviral genes that have been incorporated into the human genome (7,11,12). The current study by Kremer et al (13) in PNAS is important, for it does not just look at the association of pHERV-W envelope protein and MS but also examines potential mechanisms by which the protein causes axonal damage in MS. Axonal damage in white matter and loss of neurons/axons in cortical and deep gray matter are major determinants of disability in MS (14-16).…”
Section: Viruses and Multiple Sclerosismentioning
confidence: 96%
“…While the etiology is still unclear, the current view is that MS develops as a result of genetic predisposition and environmental triggers, with infections, smoking, childhood obesity, and deficiency of vitamin D and/or other factors related to deficient sunshine among the most likely triggers. Infections, particularly viral infections, have long been suspected as being triggers for MS and have included myxoviruses, paramyxoviruses, herpes viruses including Epstein-Barr virus (EBV), and human retroviruses (6,7). Over 30 y ago, infection with exogenous human lentiviruses was suspected (8), but differences in the presence of retroviral genome between MS and controls (9) or antibodies (10) to several retroviruses were not confirmed.…”
Section: Viruses and Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation